Synopsis of Cyatheaceae from Myanmar - Dong, Shi-Yong (Phytotaxa, 2020)
A synopsis of Cyatheaceae from Myanmar is presented for the first time. The classification of four genera in Cyatheaceae is applied and 10 species in three genera are tentatively recognized in Myanmar based on herbarium collections and previous reports. Of the 10 recognized species, Gymnosphaera henryi and G. podophylla are confirmed for the first time with distribution in Myanmar. Some misidentifications of collections in previous reports are clarified. A key to genera and species, diagnostic characters for each species, and notes involving nomenclature and species identification are provided.